Host-feeding patterns of mosquito species in Germany. Issue 1 (December 2016) - Börstler, Jessica; Jöst, Hanna; Garms, Rolf; Krüger, Andreas; Tannich, Egbert; Becker, Norbert; Schmidt-Chanasit, Jonas; Lühken, Renke
Abstract Background Mosquito-borne pathogens are of growing importance in many countries of Europe including Germany. At the same time, the transmission cycles of most mosquito-borne pathogens (e.g. viruses or filarial parasites) are not completely understood. There is especially a lack of knowledge about the vector capacity of the different mosquito species, which is strongly influenced by their host-feeding patterns. While this kind of information is important to identify the relevant vector species, e.g. to direct efficient control measures, studies about the host-feeding patterns of mosquito species in Germany are scarce and outdated. Methods Between 2012 and 2015, 775 blood-fed mosquito specimens were collected. Sampling was conducted with Heavy Duty Encephalitis Vector Survey traps, Biogents Sentinel traps, gravid traps, hand-held aspirators, sweep nets, and human-bait collection. The host species for each mosquito specimen was identified with polymerase chain reactions and subsequent Sanger sequencing of the cytochromeb gene. Results A total of 32 host species were identified for 23 mosquito species, covering 21 mammalian species (including humans) and eleven bird species. Three mosquito species accounted for nearly three quarters of all collected blood-fed mosquitoes:Aedes vexans (363 specimens, 46.8 % of all mosquito specimens), Culex pipiens pipiens formpipiens (100, 12.9 %) andOchlerotatus cantans (99, 12.8 %). Non-human mammals dominated the host species (572 specimens, 73.8 % of all mosquito specimens), followed by humans (152, 19.6 %) and birds (51, 6.6 %). The most common host species were roe deer (Capreolus capreolus ; 258 mosquito specimens, 33.3 % of all mosquito specimens, 65 % of all mosquito species), humans (Homo sapiens ; 152, 19.6 %, 90 %), cattle (Bos taurus ; 101, 13.0 %, 60 %), and wild boar (Sus scrofa ; 116, 15.0 %, 50 %). There were no statistically significant differences in the spatial-temporal host-feeding patterns of the three most common mosquito species. Conclusions Although the collected blood-fed mosquito species had a strong overlap of host species, two different host-feeding groups were identified with mosquito species feeding on (i) non-human mammals and humans or (ii) birds, non-human mammals, and humans, which make them potential vectors of pathogens only between mammals or between mammals and birds, respectively. Due to the combination of their host-feeding patterns and wide distribution in Germany, Cx. pipiens pipiens formpipiens andCx. torrentium are potentially most important vectors for pathogens transmitted from birds to humans and the speciesAe. vexans for pathogens transmitted from non-human mammals to humans. Finally, the presented study indicated a much broader host range compared to the classifications found in the literature for some of the species, which highlights the need for studies on the host-feeding patterns of mosquitoes to further assess their vector capacity and the disease ecology in Europe.